Megakaryocyte apoptosis in immune thrombocytopenia. (3rd October 2018) - Vrbensky, John R.; Nazy, Ishac; Toltl, Lisa J.; Ross, Catherine; Ivetic, Nikola; Smith, James W.; Kelton, John G.; Arnold, Donald M.
Abstract: The mechanisms of platelet underproduction in immune thrombocytopenia (ITP) remain unknown. While the number of megakaryocytes is normal or increased in ITP bone marrow, further studies of megakaryocyte integrity are needed. Megakaryocytes are responsible for the production of platelets in the bone marrow, and they are possible targets of immune-mediated injury in ITP. Since the biological process of megakaryocyte apoptosis impacts platelet production, we investigated megakaryocyte DNA fragmentation as a marker of apoptosis from ITP bone marrow biopsies. Archived bone marrow biopsy specimens from ITP patients, bone marrow specimens from controls with normal platelet counts, and bone marrow specimens from thrombocytopenic controls with myelodysplastic syndrome (MDS) were evaluated. Sections were stained with anti-CD61 for megakaryocyte enumeration, and terminal deoxynucleotidyl transferase dUTP nick-end labeling was used as an apoptotic indicator. In ITP patients, megakaryocyte apoptosis was reduced compared to nonthrombocytopenic controls. Megakaryocyte apoptosis was similarly reduced in thrombocytopenic patients with MDS. These results suggest a link between megakaryocyte apoptosis and platelet production.